FORCED SPATIAL VIBRATIONS OF A WOOD SHAPER CAUSED BY THE WEAR OF THE CUTTING TOOL - Vukov, Georgi; Slavov, Valentin; Vichev, Pavlin; Gochev, Zhivko (Innovation in Woodworking Industry and Engineering design, 2021)
This study presents the results of conducted investigations of the forced spatial vibrations of a wood shaper, caused by the wear of the cutting tool. The paper is based on a specific mechanical – mathematical model, developed by the authors, which allows studying of vibrations of this type of machinery. In this model the wood shaper is regarded as a system of three rigid bodies, which are connected by elastic and damping elements with each other and with the motionless floor. This study renders an account the mass, inertia, elastic and damping properties and geometric parameters of the machine. A necessary system of matrix differential equations is compiled and analytical solutions are presented. The results of the numerical investigations are presented. They are obtained through modern software and by using parameters of a particular machine. The results show that the amplitudes of the body’s vibrations are relatively small but the amplitudes of the spindle’s vibrations are significant especially at resonance zones.